On Vortices Initiated over West Africa and Their Impact on North Atlantic Tropical Cyclones - (:unkn) unknown (My University, 2021)
Abstract Using 38 years of the ERA-Interim dataset, an objective tracking approach is used to analyze the origin, characteristics, and cyclogenesis efficiency (CE) of synoptic-scale vortices initiated over West Africa and the Atlantic Ocean. Vortices initiated over the ocean at a given pressure level often result from a vertical expansion of a “primary” vortex track initiated earlier over West Africa. Low-level (850 hPa) primary vortices are initiated mainly in July near the Hoggar Mountains (24°N, 5°E), while midlevel (700 hPa) primary vortices are initiated mainly in August–September near the Guinea Highlands (10°N, 10°W). The CE of all these vortices is about 10% in July and 30% in August. The average CE is, however, smaller for low-level “Hoggar” vortices because they peak in July when the cyclogenesis potential index of the Atlantic Ocean is weak. Seasonal and interannual modulations of the cyclogenesis is related more to this index than to the number of vortices crossing the West African coast. Cyclogenesis is nearly equally distributed between the coast and 60°W, but the part of the cyclogenesis due to vortices initiated over West Africa decreases from 80% near the coast to about 30% at 60°W. The most probable delay between the vortex vertical expansion and cyclogenesis is 2 days, but it can be up to 10 days. This analysis also confirms previous results, such as the larger CE for vortices extending at low levels over the continent at 10°N, or the delayed and therefore west-shifted cyclogenesis of low-level “Hoggar” vortices.
Keywords: African Research